Sources in migration journalism. A qualitative approach to the Spanish context - Barranquero, Alejandro (Estudios sobre el Mensaje Periodístico, 2021)
This article explores the relationships between journalists and sources that underlie the construction of Spanish media stories on migration. In particular, we explore the leading role of citizen sources, distinguishing between migrants and the third sector organizations. Based on a documentary review and in-depth interviews with a group of 25 journalists specialized in migrations and human rights, the research addresses the journalistic uses and the cooperation and conflict relations regarding these sources from a qualitative perspective that has been scarcely explored in the field. The results reveal the necessity of establishing permanent affinity networks, while avoiding falling back on the client relationships that sometimes characterize the field.